Arthroscopic Treatment of Pigmented Villonodular Synovitis of the Elbow - Hatem B. Afana; Thomas Nau (Case Reports in Orthopedics)
Pigmented villonodular synovitis (PVNS) is a benign proliferative disorder of synovium that surrounds the joints, tendon sheaths, and bursae. The elbow is rarely affected, making it difficult to establish treatment guidelines. This article relates on a case of a male patient who presented with elbow pain and decreased range of motion. Diagnosis was established with magnetic resonance imaging (MRI) and biopsy, followed by arthroscopic removal and synovectomy. The patient was pain free shortly after surgery and gained free range of motion after six weeks. At the most recent follow-up after six months, he remained clinically well. The most recent MRI did not reveal any recurrence.